UJI DOSIS TRICOKOMPOS (HASIL FERMENTASI TRICHODERMA SPP.) DALAM MEMACU PERTUMBUHAN TIGA VARIETAS PADI (ORYZA SATIVA L.) PADA SISTEM TANAM BENIH LANGSUNG (TABELA) - WAWAN APZANI; BAHARUDDIN BAHARUDDIN; ZAINAL ARIFIN; MIRFATUL HIDAYAH; ISHAK SUNANDI (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to determine the effect of various Tricokompos doses, the effect of varieties and the interaction between these two factors on rice plants. This research used an experimental method with field trials carried out in Hamparan Papak, RT 01/RW 02, Bale Montong 1 Hamlet, Kawo Village, Pujut District, Central Lombok Regency, NTB Province from January to March 2024. The design used was a Randomized Group Design (RAK) with factorial experiment. The first factor is Tricokompos dosage with 4 levels, namely T0 (without Tricokompos), T1(5 tons/ha), T2(10 tons/ha), T3(15 tons/ha)). The second factor is using varieties with 3 levels, namely V1 (Inpari 32), V2 (Ciliwung) and V3 (Cakra Buana). The results of data analysis showed that the Tricokompos treatment factor had a significant effect on plant height parameters in all observations. The leaf number parameters observed from week 1 to week 12 had a significant effect on the Tricocompost and variety factors. Furthermore, the wet weight and dry weight parameters show a real influence. However, on the green pigment diameter of the leaves and the number of tillers there was no real influence on either the Tricocompost or Variety factors. It is also known that the number of tillers has significant results on the variety factor alone. Apart from that, the results of data analysis also showed that there was no interaction between the Tricokompos and Variety factors. The research results showed that Tricocompost resulting from fermentation of Trichoderma spp. with a dose of 15 tons/ha it can stimulate rice growth, the use of Tricokompos 10 tons/ha is the most efficient dose, and it is also known that the Inpari 32 variety shows better growth and yield compared to other varieties.